Distoseptispora pulchra sp. nov. and D. liupanshuiensis from freshwater habitats in Yunnan Province, China - Ma, Qiong; Wang, Ying; Shen, Hong-Wei; Luo, Zong-Long; Su, Xi-Jun (Phytotaxa, 2025)
During an investigation into the species diversity of lignicolous freshwater fungi in Yunnan Province, China, four strains of Distoseptispora were collected. Based on morphological characteristics and phylogenetic analysis of combined ITS, LSU, tef1-α, and rpb2 sequence data, Distoseptispora pulchra sp. nov., and one known species, D. liupanshuiensis, were identified. Distoseptispora pulchra is characterized by macronematous, mononematous, unbranched, cylindrical, septate, pale olive-brown conidiophores with monoblastic, terminal, determinate, cylindrical, pale brown to olive-brown, conidiogenous cells that produce and acrogenous, solitary, obclavate, olivaceous to pale brown, distoseptate conidia. In addition, D. liupanshuiensis is reported here for the first time from a freshwater habitat. Detailed descriptions, phylogenetic analysis results, and illustrations of both species are provided, along with a morphological comparison with related taxa.